Impact of Tourism on Andaman Islands: An Explorative Study to Understand the Problems Faced By Residents - Rita, Roshnee; Ramachandran, T. (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The Andaman Islands were the site of several of the study's operations. These places mostly consisted of those that tourists frequented and where locals who had experience with or knowledge of tourism lived. Even though the islands' tourist industry is still in its early stages of growth, the development might yet have a negative impact on the nature and traditional culture of the islands. The research attempts to present a solution to the issues that the local populace and tourists encounter in the Andaman Islands. Additionally, the study offers sufficient solutions to the issues experienced by the stakeholders. The study's findings will aid decision-makers in comprehending the issues facing these two significant tourist industry stakeholders.